The Lymphotoxin β Receptor Is Essential for Upregulation of IFN-Induced Guanylate-Binding Proteins and Survival after Toxoplasma gondii Infection - Kristina Behnke; Ursula R. Sorg; Helmut E. Gabbert; Klaus Pfeffer (Mediators of Inflammation)
Lymphotoxin β receptor (LTβR) signaling plays an important role in efficient initiation of host responses to a variety of pathogens, encompassing viruses, bacteria, and protozoans via induction of the type I interferon response. The present study reveals that after Toxoplasma gondii infection, LTβR−/− mice show a substantially reduced survival rate when compared to wild-type mice. LTβR−/− mice exhibit an increased parasite load and a more pronounced organ pathology. Also, a delayed increase of serum IL-12p40 and a failure of the protective IFNγ response in LTβR−/− mice were observed. Serum NO levels in LTβR−/− animals rose later and were markedly decreased compared to wild-type animals. At the transcriptional level, LTβR−/− animals exhibited a deregulated expression profile of several cytokines known to play a role in activation of innate immunity in T. gondii infection. Importantly, expression of the IFNγ-regulated murine guanylate-binding protein (mGBP) genes was virtually absent in the lungs of LTβR−/− mice. This demonstrates clearly that the LTβR is essential for the induction of a type II IFN-mediated immune response against T. gondii. The pronounced inability to effectively upregulate host defense effector molecules such as GBPs explains the high mortality rates of LTβR−/− animals after T. gondii infection.